Lymphocytic interstitial pneumonia and follicular bronchiolitis in children: A registry‐based case series. Issue 4 (10th February 2020) - Prenzel, Freerk; Harfst, Jacqueline; Schwerk, Nicolaus; Ahrens, Frank; Rietschel, Ernst; Schmitt‐Grohé, Sabina; Rubak, Sune M. L.; Poplawska, Krystyna; Baden, Winfried; Vogel, Mandy; Hollizeck, Sebastian; Ley‐Zaporozhan, Julia; et al.
Abstract: Objectives: Pediatric lymphocytic interstitial pneumonia (LIP) and follicular bronchiolitis (FB) are poorly characterized lymphoproliferative disorders. We present and quantify demographics, radiological and histopathologic patterns, treatments and their responses, and outcomes in non‐HIV‐infected children with LIP and FB. Methods: This structured registry‐based study included a retrospective chart review, blinded analysis of imaging studies and lung biopsies, genetic testing, and evaluation of treatments and outcomes. Results: Of the 13 patients (eight females) studied, eight had FB, four had combined LIP/FB, and one had isolated LIP; diagnoses were highly concordant between the pathologists. Most patients became symptomatic during the first 2 years of life, with a mean lag time to diagnosis of 4 years. The most common symptoms were coughing and respiratory infections (11 out of 13 each), dyspnea (10 out of 13), and wheezing (eight out of 13). Autoantibodies were found in eight out of 13 patients. In three patients, disease‐causing mutations in the COPA gene were identified. CT revealed hilar lymphadenopathy (five out of 12), ground‐glass opacity (eight out of 12), consolidation (five out of 12), and cysts (four out of 13). Systemic steroids as intravenous pulses (11 out of 13) or oral intake (10 out of 13) were the main treatments and showed high response rates of 100% and 90%, respectively. Within the mean observation period of 68 months, all children had chronic courses, eight out of 13 had severe diseases, two died, and one worsened. Conclusions: Children with LIP/FB have chronic diseases that occurred in early childhood and were commonly associated with immune dysregulation as well as high morbidity and mortality. Early diagnosis and treatment may be crucial to improve the outcome.